Key Success Factors for Sales Force Readiness: A Study of Product Launches in the Swedish Pharmaceutical Industry - Stefan C. Fraenkel (Copenhagen Business School (CBS), 2011)
This research identifies a set of key success factors for sales force readiness, for driving the success of a new product launch within the pharmaceutical industry. Drawing from the analysis of fifty product launches in the Swedish pharmaceutical market, the study has succeeded in discriminating between four types of key success factors: the key factors that are important and crucial for a successful launch; the key factors that are important yet not necessarily crucial for a successful launch; the market conditions that are most ideal for a successful launch, and finally the type of newness of the product that is most suitable for successful launch. The overall aim of the research project was to provide guidance in optimizing the sales force readiness during the launch of a new pharmaceutical product. The research question is driven by the great importance and high cost of the sales force, together with the need for the pharmaceutical companies to continuously launch new products in a marketplace with increased challenges for all parts of the business. The research approach divides the research into two main parts. The first part reviews earlier studies/findings in the literature, collects empirical data in the form of six case studies and conducts six expert interviews with the purpose of formulating a Research Model. In the second part, the Research Model and its variables are quantitatively tested against fifty launched pharmaceutical products in Sweden. The study employs a bottom-up analysis method with Partial Least Squares Analysis, being predictive in nature, rather than the more conventional top-down and hypothesis-testing approach that typically employs regression analysis methods. In order to provide both practitioners and researchers with guidance on the results, its interpretation is presented in terms of its managerial implications as well as proposals for further research.
hdl:10398/8224
Keywords: 650; Sales Force; Sales; Force Management; Product Launch; Product Introduction; New Product Launch; Pharmaceutical Industry